How to bring a building back from ruins = Jak wyprowadzić budynek z ruiny? - Błaszczyński, Tomasz; Sokołowski, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is about the renovation of the baroque palace in Żagań. The journey starts at what was once a Medieval castle and finishes in the XIX century at the villa of Żagań Princes. Now the building is a XIX century villa maintained in a baroque style. The castle was built in the Middle Ages by Silesian Piasts and rebuilt three times, first by prince Wallenstein, then by prince Lobkovic, and finally, in the XVIII century, by princess Talleyrand.
Keywords: renowacja; pałac barokowy; system odwodnienia dachu; komin; renovation; baroque palace; rainwater pipe system; chimneys